Experimental and computational study on thermoelectric generators using thermosyphons with phase change as heat exchangers. (1st April 2017) - Araiz, M.; Martínez, A.; Astrain, D.; Aranguren, P.
Highlights: Thermosyphon with phase change heat exchanger computational model. Construction and experimentation of a prototype. ±9% of maximum deviation from experimental values of the main outputs. Influence of the auxiliary equipment on the net power generation. Abstract: An important issue in thermoelectric generators is the thermal design of the heat exchangers since it can improve their performance by increasing the heat absorbed or dissipated by the thermoelectric modules. Due to its several advantages, compared to conventional dissipation systems, a thermosyphon heat exchanger with phase change is proposed to be placed on the cold side of thermoelectric generators. Some of these advantages are: high heat-transfer rates; absence of moving parts and lack of auxiliary consumption (because fans or pumps are not required); and the fact that these systems are wickless. A computational model is developed to design and predict the behaviour of this heat exchangers. Furthermore, a prototype has been built and tested in order to demonstrate its performance and validate the computational model. The model predicts the thermal resistance of the heat exchanger with a relative error in the interval [−8.09; 7.83] in the 95% of the cases. Finally, the use of thermosyphons with phase change in thermoelectric generators has been studied in a waste-heat recovery application, stating that including them on the cold side of the generators improves the net thermoelectric production by 36% compared to that obtained with finned dissipators under forced convection.